Políticas públicas educacionais para o Ensino Médio paulista durante a pandemia de COVID-19 - Ribeiro, João Carlos Cassiano (2023)
This thesis presents a qualitative research in education, carried out in a public school in the state network of São Paulo, Brazil. The general objective of the study was to understand which educational public policies were developed by the state of São Paulo to provide teaching and learning conditions during the COVID19 pandemic in the years 2020 and 2021 and what are their repercussions on the daily life of high schools? To carry out the research, a documentary study of the minutes of the Municipal and State Councils of Education and testimonials for the production of data with 6 teachers of a school unit of the state network of São Paulo was carried out. The data collected in the interviews were recorded and transcribed, categorized and later analyzed with theoretical foundations of Sociohistorical Psychology. The research results brought the following conclusions: 1) The educational policies developed were not sufficient to avoid negative impacts on student learning caused by the closure of schools and suspension of face-toface activities; 2) Social inequalities, which are historical in Brazil, increased during the pandemic, mainly due to the difficulty of accessing technologies caused by the social conditions of students; 3) The use of technological tools to carry out distance education was difficult for teachers and students. There was no preparation or training of teachers and students for its use; 4) The state's action sought to make the structure for the production and reproduction of classes viable, but it was not able to guarantee access by students to this material; and 5) The teachers' perception is that they are solely responsible for solving historical learning problems, which contributes to professional exhaustion and a feeling of isolation in relation to the work carried out by the state network, which indicates the absence of coordination and articulation of the teaching network. If we think of a Teaching System, it is necessary that the professional's performance be coordinated by the Department of Education and his performance be articulated with schools and teachers